Analisis dan Perancangan Sistem Informasi Pemasaran pada PT Bahtera Global Solusi - Suparman, Falerianus Hendratno; Nurcahyawati, Vivine; Wulandari, Sri Hariani Eko (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT. Bahtera Global Solutions is a company engaged in the provision of services and sales of IT products. IT products in the form of audio-visual products, computer, network solutions, security products, software telecommunications products and other office supplies. Marketing is one of the main factors that could affect the interests of the customer. Good marketing system and on target, may increase the purchasing power of customers and customer loyalty to the company. Thus it can increase profits for the company. Currently, the company still has obstacles in the marketing process is the lack of information regarding the products of the company making the customer trouble knowing what products are sold by the company. The company also difficult to know what products are needed promotions regularly, goods and services are most desirable, what are the needs of each customer, and promotions such as what is required of each customer. Of the above problems, the company wants to increase its marketing system. Marketing information system based 4p ie, place, price, promotion, and product marketing are needed to address the problems that occur in the company. The early stages of the design of information systems in the form of information system design can be used as a cornerstone in building a marketing information system.